The Importance of Shariah-Compliant Sustenance in ‎Maintaining Mental Well-Being: A Review‎ - Zaman, Rahim Kamarul; Saleh, Mujiburrahman Muhammad; Ab Hamid, Nur Shahidah (RABBANICA - Journal of Revealed Knowledge, 2025)
This article is a review study that explores the relationship between sharia compliance in seeking sustenance and the mental well-being of individual Muslims. In the era of materialism that challenges spiritual values, some Muslims are trapped in seeking sustenance without paying attention to the aspects of halal and haram (forbidden), which ultimately has a negative impact on the stability of the soul and mental health. Based on a qualitative method through a thematic content analysis approach, this article collects and analyses various scientific sources, including previous studies and a compilation of verses of the Quran and Hadith that discuss the concept of sustenance and psychological well-being from an Islamic perspective. The study findings show that sustenance obtained in a sharia-compliant manner contributes significantly to emotional calm, reduces stress and guilt, and strengthens the spiritual relationship with Allah. This article also concludes that the maqasid principle of Shariah plays a crucial role in ensuring a balance in life by balancing aspects of religion, reason, and the soul. This study emphasises the importance of integrating Islamic values ​​into mental health systems, education, and social policies. Therefore, having halal sustenance that complies with shariah principles not only provides economic benefits but also forms the basis for the overall psychospiritual well-being of Muslims.